Paralytic shellfish toxins in the chocolata clam, Megapitaria squalida (Bivalvia: Veneridae), in Bahía de La Paz, Gulf of California - Gárate-Lizárraga, I. (2004)
Occurrence and toxic profiles of paralytic shellfish toxins (PST) in the chocolata clam Megapitaria squalida were investigated. From December 2001 to December 2002, 25 clams were obtained monthly from Bahía de La Paz, Gulf of California. Additionally, net (20 μm) and bottle phytoplankton samples were also collected to identify toxic species. Toxins were analyzed by HPLC with post-column oxidation and fluorescence detection. Toxicity in the clam was low and varied from 0.14 to 5.46 μg/STXeq/100 g. Toxicity was detected in December, March, April, June, and August. Toxin profile was composed mainly by STX, GTX2, GTX3, dcGTX2, dcGTX3, C2, dcSTX and B1. Gymnodinium catenatum was the only PST-producing dinoflagellate identified in the phytoplankton samples throughout the study period. G. catenatum was observed mainly in net samples from December 2001 to December 2002; however, in bottle samples, G. catenatum was only observed in five months. Highest abundance (2 600 cells l-1) was observed in March and the lowest (160 cells l-1) in June. G. catenatum mainly formed two-cell chains and rarely four or eight. The presence of PST in net phytoplankton samples support the fact that G. catenatum is the main source of PST in the clams. This study represents the first report of PST toxins in the chocolata clam from Bahía de La Paz.